A multidisciplinary approach for recharge areas definition in carbonate aquifers tested on the Apuan Alps regional system, NW Tuscany-Italy - Matia Menichini; Brunella Raco; Linda Franceschi; Marco Doveri (Journal of Hydrology: Regional Studies)
Study region: Apuan Alps (NW-Tuscany, Central Italy). Study focus: Definition of the hydrogeological conceptual model of carbonate aquifer systems in order to define their recharge areas, using a multidisciplinary and integrated approach that involves geochemistry and isotopic tools. The proposed approach was tested on the Apuan Alps carbonate aquifers that contain precious groundwater resources to be protected, but their management is difficult to carry out without a detailed knowledge. The study of the groundwater hydrodynamics in terms of pathways and extension is often difficult to perform using conventional hydrogeological surveys. Geochemistry and isotopic tool can therefore provide an important contribution. However, to use such tools it is necessary to provide a characterization of the infiltration waters through which the isotopic data of the main springs can be interpreted. The paper proposes a hydrogeological approach combined with geochemical methodologies and 13C data of water and rock samples for selecting springs representative of local infiltration. New hydrological insights for the region: An isotopic characterization of infiltration water was performed, and the definition of the vertical isotope gradient specific for the area of interest was defined. By crossing this gradient with the geological structures, morphology and hydrology features of the territory, the feeding areas of two of the most important karst springs in the Apuan Alps region were delimited, thus testing the proposed methodology.